The Reality of Political Reform in Jordan and its most Prominent Obstacles in the Period (1989-2019) - Al-Mashaqbeh, Basil (Dirasat: Human and Social Sciences, 2022)
The study aimed to uncover the reality of political reform in Jordan and its most prominent obstacles in the period (1989 - 2019). To achieve this goal, a functional structural approach was adopted, which was developed by Talcott Baresons, and David Estion and Gabriel Almond, which looks at the political system as several buildings that perform Multiple and necessary functions. The study was divided into a preamble dealing with the concept of political reform and the most prominent theories explained to it in Arab and foreign literature, while the topic dealt with the reality of political reform in Jordan in the period (1989 - 2019) and the most prominent indicators of reform covered by the study period, and finally, the second topic addressed the most prominent obstacles to reform Political, whether related to parties or the social structure of Jordanian society. The study concluded that political reform in Jordan always comes after a certain crisis occurred. The reforms that Jordan witnessed in 1989 came as a result of the economic crisis that Jordan suffered from at the time, while political reforms in 2011 came as a result of the events in the Arab region during the Arab Spring revolutions. The study also showed that the weakness of political parties, in addition to the prevailing social culture in Jordanian society, which promotes loyalty to the clan or family, are among the main obstacles to political reform in Jordan.